Implementing community-based Dried Blood Spot (DBS) testing for HIV and hepatitis C: a qualitative analysis of key facilitators and ongoing challenges - James Young; Aidan Ablona; Benjamin J. Klassen; Rob Higgins; John Kim; Stephanie Lavoie; Rod Knight; Nathan J. Lachowsky (BMC, 2022)
Abstract Background In 2018, the Community-Based Research Centre (CBRC) invited gay, bisexual, trans, queer men and Two-Spirit and non-binary people (GBT2Q) at Pride Festivals across Canada to complete in-person Sex Now surveys and provide optional dried blood spot (DBS) samples screening for human immunodeficiency virus (HIV) and hepatitis C virus (HCV). As there is a lack of research evaluating the implementation of DBS sampling for GBT2Q in community settings, we aimed to evaluate this intervention, identifying key facilitators and ongoing challenges to implementing community-based DBS screening for HIV/HCV among GBT2Q. Methods We conducted sixteen one-on-one interviews with individuals involved with the community-based DBS collection protocol, including research staff, site coordinators, and volunteer DBS collectors. Most individuals involved with DBS collection were "peers" (GBT2Q-identified). The Consolidated Framework for Implementation Research (CFIR) guided our data collection and analysis. Results Interviewees felt that DBS collection was a low-barrier, cost-effective, and simple way for peers to quickly screen a large number of Sex Now respondents. Interviewees also noted that the community and peer-based aspects of the research helped drive recruitment of Sex Now respondents. Most interviewees felt that the provision of results took too long, and that some Sex Now respondents would have preferred to receive their test results immediately (e.g., rapid or point-of-care testing). Conclusion Peer-based DBS sampling can be an effective and relatively simple way to screen GBT2Q at Pride Festivals for more than one sexually transmitted and blood borne infection.